2010
DOI: 10.4061/2010/306754
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Thymidylate Synthase Gene Structure in Colorectal Cancer Patients and Its Possible Relation with the 5‐Fluorouracil Drug Response

Abstract: Thymidylate synthase (TS) catalyzes methylation of dUMP to dTMP and it is the target for the 5-Fluorouracil (5-FU) activity. Barbour et al. showed that variant structural forms of TS in tumour cell lines confer resistance to fluoropyrimidines. We planned to perform the whole TS gene structure by means of sequencing techniques in human colorectal cancer (CRC) samples to try to identify the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…While many studies have reported a correlation between high DPD expression levels and chemoresistance or poor survival rate, the prognostic value of DPD expression is still controversial in induction chemotherapy with 5-FU/cisplatin. Further studies that assess DPD levels using an enzyme assay or that examine the modification of molecular structures caused by mutations, as a previous study indicated (14), may clarify a potential role for DPD as a marker for response to induction chemotherapy with 5-FU/cisplatin.…”
Section: Discussionmentioning
confidence: 94%
“…While many studies have reported a correlation between high DPD expression levels and chemoresistance or poor survival rate, the prognostic value of DPD expression is still controversial in induction chemotherapy with 5-FU/cisplatin. Further studies that assess DPD levels using an enzyme assay or that examine the modification of molecular structures caused by mutations, as a previous study indicated (14), may clarify a potential role for DPD as a marker for response to induction chemotherapy with 5-FU/cisplatin.…”
Section: Discussionmentioning
confidence: 94%
“…These genotypic effects may contribute to individual susceptibility to BC [11,12], and have been related to pharmacogenetic variation in chemotherapy treatments [14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Elevated intracellular TS levels have been implicated in emerging resistance to fluoropyrimidines and other TS inhibitors due to the increase in transcription and translation roles of TS. Therefore, high TS expression in early-stage CRC patients is correlated to a poorer overall survival in both chemotherapy-treated and chemotherapy-untreated patients following surgery [31].…”
Section: • Positive Marginsmentioning
confidence: 99%